DEVELOPMENT AND VALIDATION OF UV-VIS SPECTROFOTOMETRY USING KIO3/KI REAGENT FOR DETERMINATION OF TOTAL ALKYLBENZYLDIMETHYLAMMONIUM CHLORIDE - Beatrice Sonja Raranta, Jessica
Global pandemic of COVID-19 has created a habit of keeping hands and surroundings clean, resulting in the rise of antiseptic and disinfectant products. Benzalkonium chloride (BKC) is a mixture of alkylbenzyldimethylammonium chloride has been widely developed into non-alcoholic antiseptics and disinfectants. With the rise of BKC products, the determination of content needs to be done to ensure the quality of these products. This study aims to develop a UV-Vis spectrophotometry method using KIO3/KI for the determination of total alkylbenzyldimethylammonium chloride content. The research was conducted in several steps including the determination of reagent composition and measurement conditions, method validation, and determination of content. The optimum condition of the reagent was obtained by using reagent 1 containing 0.005 M KI and reagent 2 containing 1 M H3PO4 and 0.001 M KIO3. Determination of content begins with mixing the sample, reagent 1, and reagent 2 in a ratio of 5:1:1 (v/v) at room temperature with an incubation time of 10 - 15 minutes and then the absorption will be measured at a wavelength of 460 nm. Validation results showed that the method has good specificity; good linearity with a correlation coefficient (r) value is 0.999 in the BKC concentration range of 4 - 18 bpj; limit of detection is 0.87 bpj and limit of quantitation is 2.05 bpj. The accuracy test result shows that the method has a percent recovery in the range of 98 - 102%; as well as intraday and interday precision test results with relative standard deviation <2%. The validated method was used on raw material samples and the comparison results of the actual concentration percent of the sample with the claim were in the range of 86.56-100.03%. The developed UV-Vis spetrophotometric method can be used for the determination of total alkylbenzyldimethylammonium chloride content in raw material samples.